(untitled) (El-Wahat Journal for Research and Studies, 2025)
This Paper Seeks To Demonstrate Silence As A Sign Of The Contractor’s Will And Impact On The Consensus Element In The Contracts. Originally, Silence Is A Mere Negative Attitude, But It Could Express The Will And Be Meaningful If The Need Arose And The Evidence And Connotations Of Customs Existed That Demonstrated Its Significance. Thus, It Serves As A Means Of Concluding The Contract And Demonstrates Its Role In Clearing Some Of The Actions Of Others, But This Is With Controls Established By The Scholars To Indicate Silence As A Sign Of Permission And Consent. Their Opinions Also Varied In The Behavior Of The Curious And The Extent Of The Impact Of The Owner’s Silence On The Effectiveness Of The Contract And Its Validity And Invalidity, So The Contract Was Considered Dependent On The Owner’s Permission. Keywords: Silence, Significance, Behavior Of The Curious, Permission, Contracts.